Commonly and Specifically Activated Defense Responses in Maize Disease Lesion Mimic Mutants Revealed by Integrated Transcriptomics and Metabolomics Analysis - Mu, Xiaohuan; Li, Jiankun; Dai, Zhuangzhuang; Xu, Liping; Fan, Tianyuan; Jing, Teng; Chen, Mengyao; Gou, Mingyue (Frontiers in Plant Science, 2021)
Disease lesion mimics (Les/les) mutants display disease-like spontaneous lesions in the absence of pathogen infection, implying the constitutive activation of defense responses. However, the genetic and biochemical bases underlying the activated defense responses in those mutants remain largely unknown. Here, we performed integrated transcriptomics and metabolomics analysis on three typical maize Les mutants Les4, Les10 and Les17 with large, medium and small lesion size respectively, thereby dissecting the activated defense responses at transcriptional and metabolomic level. 1714, 4887 and 1625 differentially expressed genes (DEGs) were identified in Les4, Les10 and Les17, respectively. Among them, 570, 3299 and 447 specific differentially expressed genes (SGs) were identified, implying specific function of each LES gene. In addition, 480 common differentially expressed genes (CGs) and 42 common differentially accumulated metabolites (CMs) were identified in all Les mutants, suggesting the robust activation of shared signaling pathways. Intriguingly, substantial analysis of the CGs indicated that genes involved in the programmed cell death, defense responses, phenylpropanoid and terpenoid biosynthesis were most commonly activated. Genes involved in photosynthetic biosynthesis, however, were generally repressed. Consistently, the dominant CMs identified were phenylpropanoids and flavonoids. Particularly, lignin, the phenylpropanoid-based polymer, was significantly increased in all 3 mutants. These data collectively imply that, transcriptional activation of defense-related gene expression, increase of phenylpropanoid, lignin, flavonoid and terpenoid biosynthesis, and inhibition of photosynthesis are general nature associated with the lesion formation and constitutively activated defense responses in those mutants. Further studies on the identified SGs and CGs will shed new light on the function of each LES genes as well as the regulatory network of defense responses in maize.